Analysis of the psychophysiological state of Ukrainian basketball players - Kyyko, Andriy; Volkova, Yuliya; Poltavets, Andrii; Yudin, Vladyslav; Kmetiuk, Dmytro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of the current study was to identify the psychophysiological characteristics of basketball players and to conduct a comparative analysis of the level of development of indicators of physical fitness of basketball players and their peers who do not play basketball. The participants of this study were Ukrainian basketball players aged 12 to 13 years, and adolescents of the same age who did not play basketball. The psychophysiological state of the participants was measured through a series of physical and psychological tests. The psychophysiological state of Ukrainian basketball players aged 12 to 13 years was significantly higher than the psychophysiological state of adolescents of the same age who did not play basketball. Basketball players had significant better results in short-distance speed tests and in speed endurance (300 meter run test). Basketball players also had significant better results in strength, measured by jumping test and pull-up bar test. Furthermore, basketball players had better results in psychological skills than those who did not play basketball, with better results in self-control, emotional stability, will to win, purposefulness, perseverance, endurance, determination, courage, initiative, discipline, and self-confidence.